Effect of Fe doping on the crystallization and electrical properties of Na0.5Bi0.5TiO3 thin film. Issue 3 (April 2015) - Feng, C.; Yang, C.H.; Sui, H.T.; Geng, F.J.; Han, Y.J.
Abstract: Na0.5 Bi0.5 Ti1− x Fe x O3− δ (abbreviated as NBTFe x, x =0.005, 0.01, 0.02 and 0.04) thin films were deposited on indium tin oxide/glass substrates via a chemical solution deposition method. The influence of Fe 2+ doping on the crystallization and electrical properties of Na0.5 Bi0.5 TiO3 was investigated. All the films crystallize into the single perovskite structure without any secondary phases. The insulating measurement reveals that 2 at% Fe 2+ doping can effectively reduce the leakage current of Na0.5 Bi0.5 TiO3 thin film by the formation of defect complexes. The enhanced ferroelectricity is obtained in NBTFe0.02 with a large remanent polarization ( P r ) of 20 μC/cm 2 due to the lowest leakage current and the distortion of TiO6 . The normalized capacitance–voltage curves of all films agree with the polarization-electric field hysteresis loops. Also, the relative dielectric constant and dissipation factor of NBTFe0.02 thin film are 450 and 0.094 at 100 kHz, respectively.